Improving Student Learning Discipline in Quran and Hadith Learning through the Implementation of the Cooperative Learning Model - Kuraisin; Kurniasih Domopili (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to improve students' learning discipline in the Qur'an Hadith subject through the implementation of the Cooperative Learning learning model. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were 25 students of class VII MTs Babussalam Lanci 1 Dompu, as well as the Qur'an Hadith subject teacher who acted as a facilitator in the learning process. The data for this study were obtained using test and observation techniques. Tests are used to measure student learning outcomes, while observations are used to analyze teacher and student learning activities during the implementation of the Cooperative Learning learning model. The data analysis techniques used in this study are qualitative and quantitative descriptive analysis, which aims to see the development of student discipline before and after the implementation of the learning model. The results of the study showed that the implementation of the Cooperative Learning learning model was able to significantly improve student learning discipline. In the first cycle, student learning discipline began to show improvement, but there were still some obstacles in student active participation. After improvements were made in the second cycle, student discipline increased significantly with more students actively participating, completing assignments on time, and showing responsibility in learning. Thus, the use of the Cooperative Learning learning model can be used as an effective learning strategy in improving students' learning discipline in the Qur'an Hadith subject. This model not only increases student involvement in learning, but also helps them develop cooperation skills and responsibility in the learning process.